Stator resistance estimation of induction motor using genetic algorithm - Nurul Syamila, Mohd Rosli (2012)
Nowadays, induction motors are mainly used in all industrial especially in plant industrial. In general, this motor is widely used because it is cheaper, easy to maintenance, no friction by brushes and their speed are easy to control compared to the direct current (DC) motor. But, the stator resistance changes continuously with the temperature of the machine. The changes can cause an error between the actual and estimated motor torques which leads to motor break down in worst cases. In order to solve this issue, a genetic algorithm method is designed to estimate the variation of stator resistance. This project is about to design genetic algorithm estimator using MATLAB software, and builds an actual induction motor using Newcastle University Drives Simulation Library. Finally these parts of Simulink diagram will be combined to estimate the variation of stator resistance.